A Theory of Merger-Driven IPOs - Hsieh, Jim; Lyandres, Evgeny; Zhdanov, Alexei (Journal of Financial and Quantitative Analysis, 2011)
We propose a model that links a firm’s decision to go public with its subsequent takeover strategy. A private bidder does not know a firm’s true valuation, which affects its gain from a potential takeover. Consequently, a private bidder pursues a suboptimal restructuring policy. An alternative route is to complete an initial public offering (IPO) first. An IPO reduces valuation uncertainty, leading to a more efficient acquisition strategy, therefore enhancing firm value. We calibrate the model using data on IPOs and mergers and acquisitions (M&As). The resulting comparative statics generate several novel qualitative and quantitative predictions, which complement the predictions of other theories linking IPOs and M&As. For example, the time it takes a newly public firm to attempt an acquisition of another firm is expected to increase in the degree of valuation uncertainty prior to the firm’s IPO and in the cost of going public, and it is expected to decrease in the valuation surprise realized at the time of the IPO. We find strong empirical support for the model’s predictions.